Carta de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Celso Barbosa, José (My University, 1921)
Proyecto de Towner de enmienda a la constitución de E.U. en favor del "status" de Puerto Rico.
Keywords: Self-determination, National--Puerto Rico.; Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Córdova Dávila, Félix, 1878-1938; Barceló, Antonio R., 1868-1938; Gómez Brioso, José, 1855-1930; Towner, Horace Mann, 1855-1932; Autodeterminación, Nacional--Puerto Rico.